2022
DOI: 10.3390/molecules27103177
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Biological Assessment of Rumex vesicarius L. Extract: Characterization of the Chemical Components and Antioxidant, Antimicrobial, Cytotoxic, and Anti-Dengue Vector Activity

Abstract: The objective of this study was to assess the biological potency and chemical composition of Rumex vesicarius aboveground parts using GC–MS. In this approach, 44 components were investigated, comprising 99.99% of the total volatile compounds. The major components were classified as fatty acids and lipids (51.36%), oxygenated hydrocarbons (33.59%), amines (7.35%), carbohydrates (6.06%), steroids (1.21%), and alkaloids (0.42%). The major components were interpreted as 1,3-dihydroxypropan-2-yl oleate (oxygenated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 63 publications
3
12
0
1
Order By: Relevance
“…These outcomes also line up with those attained by Salama et al [ 40 ], who utilized Rumex vesicarius methanolic extract against A. aegypti larvae and found that the LC 50 and LC 90 values were 19.99 and 36.12 mg L −1 after 24 h. Shehata [ 57 ] reported that petroleum ether extract from leaves of Prunus domestica and Rhamnus cathartica was more effective against Culex pipiens (LC 50 : 33.3 and 63.4 mg L −1 , respectively) than chloroform (LC 50 : 70.8 and 192.1 mg L −1 ) and methanolic extracts (LC 50 : 132.7 and 273.5 mg L −1 , respectively). Ullah et al [ 56 ] recorded LC 50 and LC 90 values of Cassia fistula and Nicotiana tabacum extracts of 50.27, 203.99, and 17.77 and 206.49 mg L −1 against larvae of Culex quinquefasciatus .…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…These outcomes also line up with those attained by Salama et al [ 40 ], who utilized Rumex vesicarius methanolic extract against A. aegypti larvae and found that the LC 50 and LC 90 values were 19.99 and 36.12 mg L −1 after 24 h. Shehata [ 57 ] reported that petroleum ether extract from leaves of Prunus domestica and Rhamnus cathartica was more effective against Culex pipiens (LC 50 : 33.3 and 63.4 mg L −1 , respectively) than chloroform (LC 50 : 70.8 and 192.1 mg L −1 ) and methanolic extracts (LC 50 : 132.7 and 273.5 mg L −1 , respectively). Ullah et al [ 56 ] recorded LC 50 and LC 90 values of Cassia fistula and Nicotiana tabacum extracts of 50.27, 203.99, and 17.77 and 206.49 mg L −1 against larvae of Culex quinquefasciatus .…”
Section: Resultssupporting
confidence: 90%
“…Several previous experiments on the essential oil and n.hexane extract of the aerial parts of R. tingitana confirm that they were potent antibacterials against both Gram positive and negative bacteria [ 17 ]. These variations in the antibacterial potential may be explained by variances in the extracts’ chemical composition caused by environmental factors, such as geographical variability, soil type, and climate [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations